2006
DOI: 10.1001/archneur.63.7.1022
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Embodiment

Abstract: Background: Patients with asomatognosia generally describe parts of their body as missing or disappeared from corporeal awareness. This disturbance is generally attributed to damage in the right posterior parietal cortex. However, recent neuroimaging and electrophysiological studies suggest that corporeal awareness and embodiment of body parts areinsteadlinkedtothepremotorcortexofbothhemispheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(31 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…However, only for the premotor cortex was a higher specificity for the mental rotation of body-related stimuli, compared to objects, specifically proposed [30,35]. Finally, based on our results and considering the role proposed for the premotor cortex in body awareness [35,36,37], we concluded that this brain area may represent one of the essential anatomical and functional bases for the motor aspect of bodily selfhood.…”
Section: Minimal Self and Bodily Self: Looking For The Basic Experiensupporting
confidence: 61%
See 1 more Smart Citation
“…However, only for the premotor cortex was a higher specificity for the mental rotation of body-related stimuli, compared to objects, specifically proposed [30,35]. Finally, based on our results and considering the role proposed for the premotor cortex in body awareness [35,36,37], we concluded that this brain area may represent one of the essential anatomical and functional bases for the motor aspect of bodily selfhood.…”
Section: Minimal Self and Bodily Self: Looking For The Basic Experiensupporting
confidence: 61%
“…Accordingly, previous neuroimaging results associated with the laterality judgment task, using both corporeal and noncorporeal stimuli, showed activation in several dominant spatial-motor processing regions, including the posterior parietal (superior parietal and the intraparietal sulcus), premotor and primary motor cortices, the supplementary motor area, and the cerebellum [28,29,30,31,32,33,34]. However, only for the premotor cortex was a higher specificity for the mental rotation of body-related stimuli, compared to objects, specifically proposed [30,35]. Finally, based on our results and considering the role proposed for the premotor cortex in body awareness [35,36,37], we concluded that this brain area may represent one of the essential anatomical and functional bases for the motor aspect of bodily selfhood.…”
Section: Minimal Self and Bodily Self: Looking For The Basic Experienmentioning
confidence: 99%
“…The authors of this study concluded that the ventral premotor cortex might represent one of the essential anatomical and functional bases for the motor aspect of bodily selfhood, also in the light of its role in integrating self-related multisensory information. This hypothesis is corroborated by clinical and functional evidence showing its systematic involvement with body awareness [70][71][72]. Thus, there seems to be a tight relationship between the bodily self-related multimodal integration carried out by the cortical motor areas specifying the motor potentialities of one's body and guiding its motor behaviour and the implicit awareness one entertains of one's body as one's own body and of one's behaviour as one's own behaviour.…”
Section: From the Bodily Self To Intersubjectivitymentioning
confidence: 70%
“…Motor, proprioceptive and visual information of arm position normally converge and are supported by a common coding, explaining for instance that one's active arm movements seem to be “visible” in complete darkness,17 that damage to the premotor cortex can lead to the visual disappearance of a hand,18 and that experimentally induced multimodal conflicts can create illusory ownership of virtual or artificial limbs 19. Moreover, illusions induced by tendon vibration at the biceps, especially when a feeling of contraction is willfully resisted, can induce the feeling that the arm is breaking, bending, curving or, indeed, create “double or multiple images” of the forearm 20.…”
Section: Discussionmentioning
confidence: 99%